Connections between object classification criteria using an ultrasonic bi-sonar system - Kreczmer, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents connections between the criteria which make three types of objects possible to be recognized, namely, edges, planes and corners. These criteria can be applied while a binaural sonar system is used. It is shown that the criteria are specific forms of a general equation. The form of the equation depends on a single coefficient. In the paper, the meaning of this coefficient is discussed. The constructions of the arrangement of objects are presented and are bound with values of the coefficient.
Keywords: ultrasonic range-finder; multi-reflection; bi-sonar system